The general reader and the academy medieval French literature and Penguin Classics - Tether, Leah ca. 20./21. Jh (Cambridge University Press, 2019)
Penguin Classics have built their reputation as one of the largest and most successful modern imprints for 'classic' texts on the notion of 'the general reader'. Following an interrogation of this idea, Leah Tether investigates the publication of medieval French literature on this list and shines a light on the drivers, motivations, negotiations and decision-making processes behind it. Focusing on the medieval French texts published between c.1956 and 2000, Tether demonstrates that, rather than Penguin's frequently cited 'general reader', a more academic market may have contributed to ensuring the success of these titles
Keywords: Penguin Books; Geschichte 500-1500; Kanon; Französisch; Literatur; Penguin classics; Penguin (Firm); History; 20th century; French literature; To 1500; History and criticism; Literature publishing; Great Britain; History; 20th century